Intraductal Papillary Mucinous Neoplasm of the Pancreas: An Update - Shu-Yuan Xiao (Scientifica)
Intraductal papillary mucinous neoplasm (IPMN) is a cystic tumor of the pancreas. The etiology is unknown, but increasing evidence suggests the involvement of several tumorigenesis pathways, including an association with hereditary syndromes. IPMN occurs more commonly in men, with the mean age at diagnosis between 64 and 67 years old. At the time of diagnosis, it may be benign, with or without dysplasia, or frankly malignant with an invasive carcinoma. Tumors arising from the main pancreatic duct are termed main-duct IPMNs, those involving the branch ducts, branch-duct IPMNs. In general, small branch-duct IPMNs are benign, particularly in asymptomatic patients, and can be safely followed. In contrast, main-duct tumors should be surgically resected and examined carefully for an invasive component. In the absence of invasion, patient’s survival is excellent, from 94 to 100%. For patients with an IPMN-associated invasive carcinoma, the prognosis overall is better than those with a de novo pancreatic ductal adenocarcinoma, with a 5-year survival of 40% to 60% in some series. However, no survival advantage can be demonstrated if the invasive component in an IPMN patient is that of the conventional tubular type (versus mucinous carcinoma). Several histomorphologic variants are recognized, although the clinical significance of this “subtyping” is not well defined.